EFFECT OF CORE CAPITAL AND SUPPLEMENTARY CAPITAL ON CAPITAL ADEQUACY RATIO (CAR) IN PT. BNI SHARIA PERIOD 2011-2018 - arjun arjun; Windari windari; ali hardana; syuaib nasution (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Based on data obtained from the financial statements of PT. BNI Syariah for the period of 2011-2018 an increase in the value of CAR is not in line with an increase in capital but an increase in CAR while capital has decreased in 2012, 2016 and 2018. A decrease in the value of CAR is not in line with a decrease in capital but a decrease in the value of CAR while capital has increased in 2017. The purpose of this study was to determine the effect of core capital and complementary capital variables partially and simultaneously on CAR at PT. BNI Syariah for the period of 2011-2018. The results of the partial research (t test) core capital has no partial effect on CAR as evidenced by tcount ttable (1,296 2,045), and supplementary capital has a negative effect on CAR as evidenced by tcount ttable ie (-2,849 - 2,045). Whereas simultaneously core capital and supplementary capital variables have simultaneous (joint) influence on CAR as evidenced by Fcount Ftable (4.060 3.33).